Weisbord’s Six Box Model: Diagnosis Perubahan Organisasi - Wardhani, Nyuwita Sari Putri; Dirgantara, M. Irhas; Maimunah, Faatin; Kadiyono, Anisa Lestari (Universitas Batanghari Jambi, 2024)
Weisbord's Six Box Model can be used to diagnose organizations in terms of goals, structure, relationships, reward systems, leadership, and mechanisms. This study aims to analyze the organization as a basic step to make changes and future organizational development using the six box model approach. Researchers conducted interviews and distributed questionnaires adapted from the Organizational Diagnosis Questionnaire developed by Preziosi. The results of the study indicate that the organization in terms of clear goals has work goals for its employees, but it will not be realistic to achieve. In terms of structure, it has a clear organizational structure but in practice it is not in accordance with the established structure chart. Relations tend to be rigid, and there are some unresolved conflicts between employees. The company currently does not yet have a fully optimal working mechanism to achieve the company's goals. The company rewards every employee who successfully meets the sales target and applies a system penalty in the form of salary deductions when the sales target is not achieved. In terms of leadership, company leaders have not been able to harmonize the other five aspects to achieve company goals. This needs to be studied further to be prepared to face the changes that will be faced in the future.